Health for All - Italia, an informative health system (Italian Journal of Public Health, 2008)
Background: On ISTAT website the informative system Health for All – Italia is available. It collects indicatorson health coming from various sources to make up a basis for constructing an organic and joint framework onthe country’s health reality. The system includes more than 4000 indicators about: demographic and socio-economic context; causes of death; life styles; disease prevention; chronic and infectious diseases; disability;health status and life expectancy; health facilities; hospital discharges by diagnosis; health care resources.The database-related software was developed by the World Health Organization to make it easier for any userto access the information available either as tables, graphs and territorial maps.Methods: The system has been built considering data coming from different sources and using, if possible,the same definitions, classifications and desegregations. Time series goes from 1980 to the last year available(which can differ among the different sources). Indicators are calculated by provinces (if possible), regions,big areas and Italy. In order to compare indicators over time and space, standardised rates are calculated,using the same population reference.For each indicator metadata are available to give users additional notes necessary to correctly read and usethe data, and publications or internet websites to examine more in-depth the argument.Results: Different kind of users find Health for All – Italia very useful for their aims: students, researchers,doctors, socio-sanitary operators, policy makers. Some examples of official reports from public institutionsare briefly described in the paper.Conclusions: The increasing number of users of Health for All – Italia make necessary the online version andan English version for international comparisons.
Keywords: informative system; health; indicator; database